2014
DOI: 10.1097/01.eja.0000435022.91954.8d
|View full text |Cite
|
Sign up to set email alerts
|

Residual neuromuscular block in type II diabetes mellitus after rocuronium

Abstract: Diabetic patients, even in the absence of complications, have an increased risk of RNMB after rocuronium administration compared with those without diabetes. Poorer glycaemic control of diabetes does not appear to increase the risk. Appropriate dose and vigilant monitoring of the neuromuscular blocker is helpful in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…From there, the differences found in the DURTOF70 and DURTOF90 (blocking recovery time to a TOF ratio ≥ 90 after the administration of a bolus dose of NMBA being significantly prolonged in type 2 diabetic patients compared with nondiabetics. These differences in the DURTOF90 have been observed both rocuronium [17] and vecuronium [18]. This parameter is strongly related to the risk of RNMB.…”
Section: Pharmacodynamic Parameters Of Neuromuscular Blockade In Diabmentioning
confidence: 81%
See 2 more Smart Citations
“…From there, the differences found in the DURTOF70 and DURTOF90 (blocking recovery time to a TOF ratio ≥ 90 after the administration of a bolus dose of NMBA being significantly prolonged in type 2 diabetic patients compared with nondiabetics. These differences in the DURTOF90 have been observed both rocuronium [17] and vecuronium [18]. This parameter is strongly related to the risk of RNMB.…”
Section: Pharmacodynamic Parameters Of Neuromuscular Blockade In Diabmentioning
confidence: 81%
“…Both studies included only diabetic patients without clinical neuropathy, renal failure or other diseases that could interfere with the NMB. Furthermore, within these diabetic patients a worse glycemic control was not observed expressed by glycated hemoglobin, this involves a greater risk of RNMB [17]. Therefore, in type 2 diabetic patients without neuropathy, we cannot know which patients are more predisposed to RNMB.…”
Section: Risk Of Residual Neuromuscular Blockade In Diabeticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Appropriate dose and vigilant monitoring of the neuromuscular blocker are recommended. 15 In another study of Yesil and colleagues it is demonstrated that phrenic nerves are affected like peripheric nerves in prediabetic and diabetic patients and reminding phrenic neuropathy in newly onset respiratory failure in diabetic and prediabetic patients without any prior existing cardiovascular or respiratory complaints is suggested. 16 That fact gives the impression that in diabetic patients without any prior existing complaints should evolve respiratory failure intra-or postoperatively due to undiagnosed phrenic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Gözlemsel prospektif bir çalışmada rokuronyum uygulamasından sonra diyabetik hastalarda diyabetik olmayan hastalara göre rezidüel nöromusküler blok riskinin artmış olduğu tespit edilmiştir [7] . Olgumuzda yaşadığımız deneyim ve ileri yaşına rağmen, yeni teşhis edilmiş diyabet ile düzensiz ilaç kullanım öyküsü altta yatan subklinik diyabetik nöropati olabileceğini düşündürmüştür.…”
Section: Olgu Sunumuunclassified